Waste Converting Into Products - Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka; Marina Bajić (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
The usage of the fossil must reduce because of a negative effect on the environment. Waste, such as municipal solid waste (MSW), which includes a lot of carbon hydrogen, is resource for chemical and energy productions. This applied study presents the methodology, which is reused the different MSW from unsorted to sorted, created by the mathematical model and the Aspen Plus®   simulator for syngas synthesised into different products: methanol, ethanol, synthetic gasoline etc. The mathematical model based on the most real and something simulated parameters. MSW was gassed by using the gasification and the purified circulated flue gas from chimney can enter as raw materials into reforming for syngas production. After the reforming was synthesised the syngas, which is raw material for many products, such as methanol, ethanol and/or synthetic gasoline. During the processes are generated a lot of hydrogen, which can be cleaned and produced as co-product. An existing methanol process can be replaced natural gas with waste different for the methanol or ethanol or synthetic gasoline productions, which could reduce the garbage and CO2 emission of 0.106·106 t/a and of 0.084 ·106 t/a.